(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Postpartum fatigue has a negative effect on the physical and mental conditions of a mother and mother and baby interactions. The process of breastfeeding is often the cause of postpartum fatigue. This study aimed to determine the effect of breastfeeding pillows on maternal fatigue and the mother and baby response during breastfeeding (MBA). Methods: This research was a quasi-experimental study with nonequivalent (pretest and posttest) with a control group design. The research was conducted between July – February 2017 in the areas of Mantrijeron and Umbulharjo 1 Public Health Centers in Yogyakarta, Indonesia. Determination of samples was based on a screening process that was done purposively. The number of research samples were 60 respondents for the intervention and control group, ethical approval number was with Ref: KE/FK/0888/EC/2017. Results: There were significant differences in MBA values ( p = 0.000), and fatigue (p = 0.002) pretest and posttest in the intervention group compared to the control group. The mean difference between the pretest and posttest MBA scores in the intervention group was higher (1.93) than in the control group (0.53). The mean difference in the value of the pretest and posttest for fatigue in the intervention group was higher, which was equal to (5.16) than in the control group (1.93). Conclusions: There is a positive influence the use of breastfeeding pillows on the value of maternal fatigue and the response of the mother and baby during breastfeeding.